Using the Stallings Observation System to Investigate Time on Task in Four Countries - Stallings, Jane A.; Knight, Stephanie L.; Markham, David (World Bank, Washington, DC, 2014)
This paper presents the history of the Stallings Observation System (SOS) and describes the adaptation of the SOS instrument, training for its use in international settings, and results from four countries of the World Bank International Time on Task (ITOT) project. The ITOT project had three major goals: 1) to discover how instructional time is used at different levels in certain countries, particularly in rural and low income areas; 2) to identify obstacles to optimal use of instructional time; and 3) to encourage governments to take the necessary measures to provide students with optimal time for learning (Abadzi, Millot, & Prouty, 2004). In order to address ITOT at the classroom level, a pilot study in Tunisia was conducted that targeted four related objectives: 1) adaptation of the Stallings snapshot observation instrument for use in project classrooms; 2) design and implementation of training for observers; 3) determination of reliability and validity of observation procedures; and 4) generation of a sample profile of classrooms in a Tunisian elementary school. This paper summarizes the training and findings from the initial pilot study of time usage at the classroom level conducted in Tunisia in January, 2004 and the training and results from subsequent ITOT studies in four countries: Tunisia, Morocco, Ghana, and Brazil. More specifically, sections of the paper provide an overview of the research on effective use of instructional time using the Stallings instrument, description of the adaptation of the Stallings Snapshot observation instrument for use in the project, a summary of the training and procedures developed for the pilot study and implemented in four countries, and the results and conclusions from the observational studies in four countries.